Prove: EG bisects HF and HF bisects EG.
Answer:
Given : EFGH is a Parallelogram
Prove : EG Bisects HF , HF Bisects EG
Step-by-step explanation:
Proof
Check image below
Answer:
Given Parallelogram EFGH
EG bisects HF and HF bisects EG, if and only if both the diagnols have same mid point.
Step-by-step explanation:
Step 01:
Let
E be the point (a,b)
F be the point (a',b)
G be the point (a',b')
H be the point (a,b')
Step 02:
Now find mid points of EG and HF
mid point of EG = ( , ) and
mid point of HF = ( , )
Since addition is commutative, and they have the same mid-point, so they bisect each other.
Answer:
120
Step-by-step explanation:
Answer:
The slope is 9.
Step-by-step explanation:
Slope intercept form is y = mx + b
y = how far up
x = how far along
m = slope
b = value of y when x = 0
y = 9x - 2
The m is replaced by 9 which is the slope.